Why SF6 eats electrons: identifying high electrical strength molecules from their electron collision properties. (22nd January 2021) - Wang, Chunlin; Cooper, Bridgette; Wu, Yi; Sun, Hao; Tennyson, Jonathan
Abstract: The electrical strength of a molecule is a measure of its ability to act as an insulator and to absorb electrons. SF6 is a high electric strength gas. This work tries to explain why molecules like SF6 have a high electrical strength from the perspective of electron molecule scattering. The presence of a very low energy (<<1 eV) totally symmetric state in form of a very low-lying resonance, virtual state or very weakly bound state appears to be crucial. R-matrix calculations performed at the static exchange plus polarisation (SEP) level are performed for a number of molecules that show a range of electrical strengths. SEP calculations suggest that SF6 has a strong low energy 2 A g resonance feature which becomes a weakly bound state as more virtual orbitals are included in the calculation. High electrical strength molecules such as CCl4, CCl3 F and CCl2 F2 also have a totally-symmetric low-energy resonance, while the low electrical strength molecules such as CH4, CH3 F…CF4 and CClF3, do not show any resonance behaviour in the low energy region. It is suggested that this low energy feature can be used as an indicator when searching for new molecules with high electrical strength facilitating searches for new gases which could provide an alternative to SF6 .